Genetic characterization of group A acetylsaponin‐deficient mutants from wild soybean (Glycine soja Sieb. and Zucc.). Issue 3 (21st April 2015) - Krishnamurthy, Panneerselvam; Lee, Jeong‐Dong; Ha, Bo‐Keun; Chae, Jong‐Hyun; Song, Jong Tae; Tsukamoto, Chigen; Singh, Ram J.; Chung, Gyuhwa; Link, W.
Abstract Group A acetylsaponins are the main causative components for bitter and astringent tastes of soybean (Glycine max). In this study, we examined the genetic nature of the absence of group A acetylsaponins in 12 Korean wild soybean (Glycine soja) accessions. In all 12 accessions, the coding region (1431‐bp) of Sg‐1 locus was identical with Sg‐1a, which adds the xylose sugar moiety at the terminal position of the C‐22 sugar chain of SS‐A, except one nucleotide (G→A change) at +948th position. This point mutation results in change of one amino acid from tryptophan (TGG) to stop codon (TGA). We observed that the mutated Sg‐1 was controlled by a single recessive gene (sg‐10‐a1). This gene was mapped between BARCSOYSSR_07_1561 and BARCSOYSSR_07_1598 on soybean chromosome 7. Our study demonstrated that the mutated Sg‐1 gene in Korean wild soybeans is genetically different from those identified in Japanese soybean cultivar 'Kinusayaka' and wild soybean JP‐36121. We believe that the new Sg‐1 mutants can also be utilized to produce a new soybean variety without bitter and astringent properties.